A phenotype combining hidradenitis suppurativa with Dowling–Degos disease caused by a founder mutation in PSENEN. (18th December 2017) - Pavlovsky, M.; Sarig, O.; Eskin‐Schwartz, M.; Malchin, N.; Bochner, R.; Mohamad, J.; Gat, A.; Peled, A.; Hafner, A.; Sprecher, E.
Summary: Background: Dowling–Degos disease (DDD), featuring reticulate pigmentation, and familial hidradenitis suppurativa (HS) share many clinical features including autosomal dominant inheritance, flexural location and follicular defects. The coexistence of the two disorders was recently found to result from mutations in PSENEN, encoding the γ‐secretase subunit protein presenilin enhancer. Objectives: To investigate PSENEN mutations in a series of four unrelated patients who presented with combined DDD and HS. Methods: Mutation and haplotype analysis of PSENEN by polymerase chain reaction, and cellular assays investigating the Notch signalling pathway. Results: Here we report four families of Jewish Ashkenazi origin who presented with clinical features characteristic of both disorders. All patients were found to carry the same, heterozygous mutation in PSENEN (c.168T>G, p.Y56X). Haplotype analysis revealed that the mutation originated from a common ancestor. Genes associated with DDD, as well as HS, have been shown to encode important regulators of Notch signalling. Accordingly, using a reporter assay, we demonstrated decreased Notch activity in a patient's keratinocytes. Conclusions: The present data confirm the genetic basis of the combined DDD‐HS phenotype and suggest that Notch signalling may play a central role in the pathogenesis of this rare condition. Abstract : What's already known about this topic? The association of Dowling–Degos disease (DDD) and hidradenitis suppurativa (HS) has been reported. Patients with both diseases carry mutations in PSENEN . What does this study add? We report a novel founder mutation in PSENEN causing a phenotype combining DDD and HS in four families. The mutation was found to result in altered Notch signalling. What is the translational message? This study expands the spectrum of PSENEN mutations associated with HS‐DDD. Notch signalling may play a role in the pathogenesis of this combined disorder. Linked Comment:  McGrath. Br J Dermatol 2018;178 :328 . Plain language summary available online Respond to this article